LITERASI EKONOMI DAN KEGIATAN P5 KEWIRAUSAHAAN SEBAGAI FAKTOR PENDORONG MINAT BERWIRAUSAHA PESERTA DIDIK - Rezya Marsanda Aprilia; Astri Srigustini; Kurniawan Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of economic literacy and P5 entrepreneurship activities on students' interest in entrepreneurship. This study uses a survey method and quantitative research with an explanatory design. This study's population consisted of all tenth grade students (391 in total). The sampling technique used is probability sampling by simple random sampling of samples taken by 198 students. Data were obtained through the distribution of questionnaires, and the data analysis techniques used were multiple linear regression and hypothesis testing. The linear regression value for this study is Y = 28,184 + 0,538 + 0,180. Based on the results of statistical calculations, economic literacy has a positive and significant effect on entrepreneurial interest, and P5 entrepreneurship activities have no effect on entrepreneurial interest. Meanwhile, economic literacy and P5 Entrepreneurship Activities had an effect on entrepreneurial interest, with a coefficient of determination () value of 0.553 (55%).